(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: Nosocomial bacteria are bacteria that cause diseases acquired from the hospital environments. Aim: This study looked into profile of bacterial pathogens associated with nosocomial infections in hospitals within Makurdi metropolis. Result: A total of 71 bacterial pathogens were encountered from 240 samples analysed from three hospitals in Makurdi metropolis. Of the 71 isolates, 46(64.8%) were Gram positive and 25(35.2%) were Gram negative. The Gram positive constituting S. aureus (50.70%) and staphylococcus spp (14.08%) while the Gram negative constituting E. coli (15.50%), klebsiella spp (7.04%) and P. aeruginosa (12.68%). Out of 21(29.58%) isolates cultured from hand swabs, the bacterial pathogens from hand swab at F M C was the highest 12(57.14%) followed by C H M 5(23.81%) while B M M C has the least profile of 4(19.05%). With regards to hospital air, the highest profile of nosocomial bacteria was also from F M C 8(61.54%), followed by B M M C 4(30.77%) while C H M had just only one isolate 1(7.69%). Of 21(29.58%) isolates from B M M C; 10(47.62%) S. aureus, 4(19.05%) Staphylococcus spp, 2(9.52%) P. aeruginosa and 5(23.81%) Escherichia coli were obtained. In C H M, out of 18(25.35%) bacterial pathogens evolved constituting 12(66.67%) S. aureus, 2(11.11%) Staphylococcus spp, 1(5.56%) P. aeruginosa and 3(16.67%) E. coli. Whereas, the profile of 32(45.07) isolates in Federal Medical Centre Makurdi constituting 14(43.75%) S. aureus, 4(12.50%) Staphylococcus spp, 6(18.75%) P. aeruginosa, 3(9.38%) E. coli and 5(15.63%) Klebsiella spp were obtained. The antibiotic susceptibility pattern to Staphylococcus spp reveals that the highest level of sensitivity were demonstrated by Cloxacillin and Ofloxacin with 50%, followed by Augumentin and Cefuroxime with 40%, Gentamicin (30%), Erythromycin (20%) and least sensitivity with Ceftriazone (10%) while Ceftazidime has the highest resistance recorded 0% sensitivity. E. coli has the highest sensitivity on Ceftazidime having 81.8% and Gentamicin 63.6%, Ofloxacin also displayed a high level of sensitivity to isolates tested with 63.6% sensitive, follow by Cefuroxime (45.5%). Conclusion: This study showed that nosocomial bacterial pathogens particularly, S. aureus, P. aeruginosa, Staphylococcus spp and enteric bacteria, E. coli and Klebsiella spp are the predominant pathogens associated with infections acquired in hospital environment.So, information on resistance patterns of isolates encountered in this study will assist the clinicians in making improvement in management of nosocomial infections. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.368-378